An Analysis of the Development of Students' Critical Thinking Skills in the English Language Study Program at Nahdlatul Ulama Islamic University Jepara - Mahalli Mahalli (CV. Creative Tugu Pena, 2026)
This study aims to analyze the development of students' critical thinking skills through the design, instructional strategies, and evaluation of English argumentative writing instruction in the English Education Program (PBI) at Universitas Islam Nahdlatul Ulama Jepara. A qualitative research approach was employed, involving PBI students and lecturers selected through purposive sampling. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed using thematic analysis. The findings reveal that critical thinking development is systematically embedded in the selection of contextual and controversial teaching materials, the implementation of student-centered learning strategies such as group discussions, project-based learning, and text analysis, as well as the application of continuous formative assessment. Evaluation practices extend beyond written examinations to include project-based assignments, peer review, and portfolio assessment supported by clear assessment rubrics. These practices enable lecturers to monitor students' analytical development and provide constructive feedback. The study concludes that fostering critical thinking in English argumentative writing requires a holistic and integrated approach that aligns teaching materials, instructional strategies, and evaluation practices with the principles of the Merdeka Curriculum. These findings offer practical implications for EFL educators and curriculum designers by demonstrating that critical thinking development is most effective when it is structurally embedded across all instructional components rather than treated as an isolated skill. This study contributes to the existing literature by providing an empirically grounded framework for integrating higher-order thinking into EFL writing instruction within flexible, autonomy-oriented curriculum contexts, particularly in Indonesian higher education settings.